1989
DOI: 10.1161/01.res.64.5.915
|View full text |Cite
|
Sign up to set email alerts
|

Relation between longitudinal, circumferential, and oblique shortening and torsional deformation in the left ventricle of the transplanted human heart.

Abstract: The present study was designed to investigate the anisotropy of systolic chord shortening hi the lateral, inferior, septal, and anterior regions of the human left ventricle. At the time of surgery, 12 miniature radiopaque markers were implanted into the left ventricular midwall of the donor heart in 15 cardiac transplant recipients. Postoperative biplane cineradiograms were computeranalyzed to yield the three-dimensional coordinates of these markers at 16.7-msec intervals. In each of the four left ventricular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
150
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 221 publications
(160 citation statements)
references
References 72 publications
9
150
0
Order By: Relevance
“…Contraction of these oblique and spirally orientated fibres causes “torsion” such that when viewed from the apex, systolic contraction of the ventricle is characterised by the counterclockwise rotation of the apex and clockwise rotation of the base 146 . During isovolumic contraction, brief apical clockwise rotation occurs that reverses rapidly becoming counterclockwise during LV ejection 147 , 148 , followed by untwisting (clockwise rotation) during early diastole. In contrast, rotation of the base is lower in magnitude and opposite in direction.…”
Section: Torsion/twist Mechanicsmentioning
confidence: 99%
“…Contraction of these oblique and spirally orientated fibres causes “torsion” such that when viewed from the apex, systolic contraction of the ventricle is characterised by the counterclockwise rotation of the apex and clockwise rotation of the base 146 . During isovolumic contraction, brief apical clockwise rotation occurs that reverses rapidly becoming counterclockwise during LV ejection 147 , 148 , followed by untwisting (clockwise rotation) during early diastole. In contrast, rotation of the base is lower in magnitude and opposite in direction.…”
Section: Torsion/twist Mechanicsmentioning
confidence: 99%
“…With strain data based on implanted markers (11,12) and in previous studies with MR tagging (14 -19), some normal human heart strain values have been calculated. Ingels et al (12) implanted arrays of tantalum screws in 15 transplanted hearts and found the longitudinal peak strain at the midventricular level to range from 12% Ϯ 5% to 13% Ϯ 6% compared with 16.4% Ϯ 1.6% to 19.2% Ϯ 1.6% in our study, and the peak circumferential strain at the middle ventricular level to range from 15% Ϯ 4% to 19% Ϯ 5% compared with the 16% Ϯ 1.7% to 20.8% Ϯ 2.7% calculated in this study. The strain values in the study by Ingels et al (12) were qualitatively similar but slightly lower in magnitude than those in the present study.…”
Section: Longitudinal and Circumferential Strainmentioning
confidence: 99%
“…Ingels et al (12) implanted arrays of tantalum screws in 15 transplanted hearts and found the longitudinal peak strain at the midventricular level to range from 12% Ϯ 5% to 13% Ϯ 6% compared with 16.4% Ϯ 1.6% to 19.2% Ϯ 1.6% in our study, and the peak circumferential strain at the middle ventricular level to range from 15% Ϯ 4% to 19% Ϯ 5% compared with the 16% Ϯ 1.7% to 20.8% Ϯ 2.7% calculated in this study. The strain values in the study by Ingels et al (12) were qualitatively similar but slightly lower in magnitude than those in the present study. Limitations of the implantation method, such as changes from surgical transplantation, presence of metal helices in myocardium, and low spatial resolution, may account for these differences.…”
Section: Longitudinal and Circumferential Strainmentioning
confidence: 99%
“…In several reports torsion and contraction were investigated separately (Buchalter et d., 1994;Gibbons Kroeker et al, 1993;Hansen et al, 1991;Ingels et al, 1989;Ohayon and Chadwick, 1988;Rademakers et al, 1992;Young et ul., 1994). Arts et al (1984) measured the relation between torsion and contraction echographically in dogs.…”
Section: Introductionmentioning
confidence: 99%